Hubungan Mutu Pelayanan Puskesmas Standar MTBS dengan Pemberian Obat Untuk Kesembuhan Anak Balita di Wilayah Kerja Puskesmas Koto Baru Kab. Dharmasraya - Rati Purwati; Ita Dwiaini (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Diseases that cause 7 out of every 10 deaths of children under five in developing countries including Indonesia are ARI, Diarrhea, Measles, Malaria and Malnutrition. The implementation of the IMCI standard has been carried out at the Koto Baru health center in Dharmasraya Regency, but no evaluation has been carried out on the relationship between the service quality of the Integrated Management of Sick Toddler Health Center standard with the recovery status of children under five. The purpose of this study was to determine the effectiveness of treating children under five at the Koto Baru Public Health Center with standard IMCI service quality in Dharmasraya Regency. The form of this research is observational using quantitative with case control design. Subjects were toddlers aged 2 months to 5 years, a total of 160 people consisted of 80 children under five who did not recover as the case group and 80 children under five who recovered as the control group. Samples were selected according to inclusion and exclusion criteria. Bivariable analysis using chi-square test and multivariable test with logistic regression. Bivariable analysis showed that there was a significant relationship between the service quality of the MTBS standard health center and the recovery status of children under five with a p value of 0.05). Public health centers with good service quality (according to the IMCI standard) have a higher cure rate for children under five than those with non-standard IMCI service quality.